Politeness in interactions between middle-aged Malaysian Chinese and their aging parents / Koh Sin Yong - Koh , Sin Yong (2018)
The study examines politeness in the interactions between middle-aged Malaysian Chinese and their aging parents. It aims to investigate the employment of politeness strategies between middle-aged Malaysian Chinese and their aging parents during mealtime conversations. The realisation of the different politeness strategies used in the interactions between middle-aged Malaysian Chinese and their aging parents are explored. This study also investigates the types of politeness strategies that appear in the illocutionary acts of directives and commissives used by the participants of the study. Brown and Levinson’s (1987) model of politeness and Searle’s (1969) classifications of speech acts are adopted as the theoretical framework of the research. A qualitative approach is employed to analyse five sets of mealtime conversations. The findings reveal that the most commonly used politeness strategies among the family members of the study are bald-on-record and positive politeness strategies, whereas negative politeness and off-record strategies are less often used. The aging parents employed more bald-on-record strategies to their middle-aged children, while middle-aged children employed more positive politeness strategies to their aging parents.